112k views
0 votes
Simplify these expressions

9(w+6)+4 f+4(f-2)

2m+7+9m 3.1(p-2.7)

5(3+m)-7

1 Answer

2 votes

Answer:

9w+8f+46, 11m+7, 3.1p-8.37, 8+5m.

Explanation:

9(w+6)+4f+4(f-2)

9w+54+4f+4f-8

9w+54-8+8f

9w+46+8f

---------------------

2m+7+9m=2m+9m+7=11m+7

-------------------------------------------

3.1(p-2.7)=3.1p-8.37

---------------------------

5(3+m)-7=15+5m-7=8+5m

User Aaron Cooley
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.